Vulnerable Attitude of Road user using Fuzzy Matrix Technique (International Journal of Engineering and Computer Science, 2017)
Road collision is one among the major cause of increase death toll around the world. An increasing heavy burden of traffic on roads thus lead to road accidents. The purpose of this study is to determine the age group of people who violates traffic rules and regulations to engage themselves and others in road traffic collision using fuzzy matrix technique. This paper is constituted into four division with introduction, procedure for combined effective time dependent data matrix, estimation of maximum age of the vulnerable road user, conclusion and suggestion based on the study.